The role of cluster analysis in promoting sustainable development in low-density destinations - Isabel Vieira; Ana Rodrigues; Didiana Fernandes (Millenium, 2025)
Introduction: Research on residents' perceptions of sustainable tourism development (STD) has focused mainly on high-density areas, with little attention to emerging destinations. This study analyzes residents' perspectives in Lamego, a historic town in northern Portugal within the Douro World Heritage area.